A tuberculin skin test survey among healthcare workers in two public tertiary care hospitals in Bangladesh. - Md Saiful Islam; Abrar Ahmad Chughtai; Arifa Nazneen; Kamal Ibne Amin Chowdhury; Muhammad Tauhidul Islam; Sayeeda Tarannum; S M Hasibul Islam; Sayera Banu; Holly Seale (PLoS ONE)
In Bangladesh, there is currently no data on the burden of latent TB infection (LTBI) amongst hospital healthcare workers (HCWs). This study aimed to determine the prevalence of LTBI and compare the prevalence among HCWs in two public tertiary care hospitals. Between September 2018 and August 2019, we conducted a cross-sectional study in two public tertiary care general hospitals. Using a survey and tuberculin skin test (TST), we assessed risk factors for LTBI, adjusting for known and plausible confounders. In addition, a facility assessment was undertaken to understand the implementation of relevant IPC measures. The prevalence of LTBI among HCWs was 42%. HCWs spent a median of 6 hours (SD = 1.76, IQR 2.00) per day and attended an average of 1.87 pulmonary TB patients per week. HCWs did not receive any TB IPC training, the wards lacked a symptom checklist to screen patients for TB, and no masks were available for coughing patients. Seventy-seven percent reportedly did not use any facial protection (masks or respirators) while caring for patients. In the multivariable model adjusting for hospital level clustering effect, TST positivity was significantly higher among HCWs aged 35-45 years (aOR1.36, 95% CI: 1.06-1.73) and with >3 years of service (aOR 1.67, 95% CI: 1.62-1.72). HCWs working in the medicine ward had 3.65 (95% CI: 2.20-6.05) times, and HCWs in the gynecology and obstetrics ward had 2.46 (95% CI: 1.42-4.27) times higher odds of TST positivity compared to HCWs working in administrative areas. This study identified high prevalence of LTBI among HCWs. This may be due to the level of exposure to pulmonary TB patients, and/or limited use of personal protective equipment along with poor implementation of TB IPC in the hospitals. Considering the high prevalence of LTBI, we recommend the national TB program consider providing preventative therapy to the HCWs as the high-risk group, and implement TB IPC in the hospitals.